2014
DOI: 10.4028/www.scientific.net/kem.609-610.856
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of a Novel Locking Mechanism of MEMS Safety and Arming Device

Abstract: In this paper, a novel locking mechanism of MEMS S&A device has been proposed. Through establishing the mathematical model of the motion for the slider and simulating the physical model by the non-linear dynamic mechanics, appropriate novel locking mechanism is designed to meet two items, one item is the slider can slide to the bottom under the launch overload conditions; the other item is the slider cant be pulled back after the launch overload conditions. Through the experiment, the feasibility of the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Therefore, the explosion-suppression-mechanism performance of the MEMS S&A device must be studied. A fluid–solid coupling algorithm is used mainly to study the dynamic response of MEMS S&A devices in the explosion-suppression-mechanism field [12].…”
Section: Parametric Calculation Methods Of Mems Sanda Device Under Dementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the explosion-suppression-mechanism performance of the MEMS S&A device must be studied. A fluid–solid coupling algorithm is used mainly to study the dynamic response of MEMS S&A devices in the explosion-suppression-mechanism field [12].…”
Section: Parametric Calculation Methods Of Mems Sanda Device Under Dementioning
confidence: 99%
“…In 2014, Wang Fufu et al invented a MEMS security-system structure [11] that is now used primarily for fuze safety systems. In their design, the safety system is placed perpendicular to the fuze spring axis and double safety is used [12,13], whereby the system is designed to have the protective function of release from a long distance. Although this MEMS S&A device exhibits a high reliability and stability and a low power consumption [14,15], because of its special base materials it possesses a poor explosion-suppression-mechanism performance and cannot absorb the energy generated by the explosion-suppression mechanism [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the U.S. fuze annual conferences reported that the performance of on-chip-based S&A device is tested using the missile warhead at present [26][27][28][29][30], and the development trend of fuze technology is on-chip integration of machinery, electronics and pyrotechnics in the future. On this basis, our term developed a MEMS S&A device used in small-caliber ammunition innovatively, and the concrete structure as shown in Figure 2 [31][32][33]. The size of the device isΦ14×15 mm (except detonating tube, electric detonator and electric thruster).…”
Section: Introductionmentioning
confidence: 99%